Dietary fiber and other functional components in two varieties of crude and extruded kiwicha (Amaranthus caudatus) - Repo-Carrasco-Valencia R. (2009)
Financing from CONCYTEC (Concejo Nacional de Ciencia, Tecnologia e Innovacion tecnologica) is gratefully acknowledged.